Third Five-Year Plan of Andhra Pradesh Annual Plan for 1961-62 - Planning Commission (Planning Commission, 1961)
A sum of Rs 6.25 lakhs for 1961-66 and Rs. 0.80 lakh for 1961-62 will be provided on these centrally sponsored schemes towards State’s share and this expenditure will be met by adjustment from other schemes during the course of implementation of the plan.
Planning and Local Administration Department, Andhra Pradesh